Perioperative dental screening and treatment in patients undergoing cardiothoracic surgery and interventional cardiovascular procedures. A consensus report based on RAND/UCLA methodology. (20th December 2019) - Cotti, E.; Cairo, F.; Bassareo, P. P.; Fonzar, F.; Venturi, M.; Landi, L.; Parolari, A.; Franco, V.; Fabiani, C.; Barili, F.; Di Lenarda, A.; Gulizia, M.; et al.
Abstract: Aim: To reach a consensus on a consistent strategy to adopt when screening patients for dental/periodontal infections and on the feasibility of providing dental treatment before cardiothoracic surgery, cardiovascular surgery or other cardiovascular invasive procedures. Methodology: A panel of experts from six Italian scientific societies was created. The deliberations of the panel were based on the RAND method. From an initial systematic literature review, it became clear that a consensually validated protocol for the reproducible dental screening of patients awaiting cardiac interventions was considered mandatory by professionals with expertise in the dental, cardiologic and cardiac surgery areas. However, a systematic review also concluded that the treatment options to be provided, their prognosis and timing in relation to the physical condition of patients, had never been defined. Following the systematic review, several fundamental questions were generated. The panel was divided into two working groups each of which produced documents that addressed the topic and which were subsequently used to generate a questionnaire. Each member of the panel completed the questionnaire independently, and then, a panel discussion was held to reach a consensus on how best to manage patients with dental/periodontal infections who were awaiting invasive cardiac procedures. Results: A high level of agreement was reached regarding all the items on the questionnaire, and each of the clinical questions formulated were answered. Three tables were created which can be used to generate a useful tool to provide standardized dental/periodontal screening of patients undergoing elective cardiovascular interventions and to summarize both the possible oral and cardiovascular conditions of the patient and the timing available for the procedures considered. Conclusions: Upon publication of this consensus document, the dissemination of the information to a wide dental and cardiac audience should commence. The authors hope that this consensus will become a model for the development of a dedicated protocol, ideally usable by heart and dental teams in the pre‐interventional preparation phase.